The Effectiveness of the Direct Instruction Learning Model on the Ability of Badminton Basic Techniques at Sma Negeri 1 Citeureup - Rahman, Fajrul; Purnamaningsih, Ine Rahayu; Dimyati, Akhmad (FKIP - Universitas Riau, 2024)
The education process is a system consisting of input, process and output. Input is students who will carry out learning activities, the process is an activity of teaching and learning while output is the result of the process carried out. From the implementation of the educational process, it is expected to produce high quality and competitive human resources to face competition in this era of globalization. The purpose of this study was to determine the effectiveness of the direct instruction model in improving the ability of basic badminton techniques in students at SMAN 1 Citeureup, This research approach is a quantitative approach with experimental methods, for the population itself is 10th grade students at SMA Negeri 1 Citeureup, this study used a one group pretest posttest design. the results showed a significant increase in the average before and after treatment, increasing from 5.5 to 9.7 with an N_Gain value of 64.29%. Furthermore, the significance value calculated from the test of the significance value calculated from the test of the pretest posttest design. Furthermore, the calculated significance value of hypothesis testing is smaller than the significant level (α), which is 0.000 <0.05. The calculation of descriptive statistics of the average pretest and Posttest shows that the direct learning model has a positive effect on improving the basic badminton skills of students at SMAN 1 Citeureup.